2009
DOI: 10.1039/b900341j
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic immobilization of organometallic species: biosilification of NCN- and PCP-pincer metal species using demosponge axial filaments

Abstract: Silicatein protein filaments isolated from marine demosponges have been used to influence the condensation of siloxanes bearing organometallic pincer complexes. The siliceous material is formed under remarkably mild conditions and the organometallic pincer becomes an intrinsic part of the silica. The immobilisation of a metal pincer, which acts as a sensor and initial results on the immobilisation of a pre-catalytic pincer species are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Purified filaments of silicatein can be converted to catalysts for processes as diverse as Heck reactions or binding of SO 2 gas; this occurs by incubating them with alkoxy silanes with metallated pincer complexes, integrating the pincer into silica [143]. In the first description of an enzymatically enhanced organometallic condensation, recombinant silicatein (modestly—only 2-fold) catalyzes the condensation of alkoxy silanes at neutral pH and ambient temperature to yield silicones like straight-chained dimethylsiloxane [144].…”
Section: Biotechnological Applications Of Silicifying Proteins Andmentioning
confidence: 99%
“…Purified filaments of silicatein can be converted to catalysts for processes as diverse as Heck reactions or binding of SO 2 gas; this occurs by incubating them with alkoxy silanes with metallated pincer complexes, integrating the pincer into silica [143]. In the first description of an enzymatically enhanced organometallic condensation, recombinant silicatein (modestly—only 2-fold) catalyzes the condensation of alkoxy silanes at neutral pH and ambient temperature to yield silicones like straight-chained dimethylsiloxane [144].…”
Section: Biotechnological Applications Of Silicifying Proteins Andmentioning
confidence: 99%
“…It was shown that (recombinant) silicatein is capable of precipitating various transition metal oxides from different solute precursors, e.g., gallium oxide from gallium nitrate [160] or anatase from a soluble lactato-titanium complex [161]. Silicatein is capable of processing not only metal-centred substrates, but also catalyzing polymerization to give biodegradable poly(L)-lactide [162], silicones [163], or gas-sensing pincer metal complexes [164]. Tremel and co-workers pushed this idea further, by binding silicatein on surfaces by various techniques to give functionalized metals, e.g., gold-thiolate surfaces by means of a nitrilotriacetic acid (NTA)-linker system, and metal oxide-surfaces by an NTA-bearing capping agent [165,166,167,168].…”
Section: From Creatures To Conceptsmentioning
confidence: 99%
“…Pt-silica prepared using this method were used for SO 2 sensing while Pd-silica hybrids were successfully tested for Heck reactions for carbon-carbon coupling. 214…”
Section: Supporting Metals and Functional Metallic Nanoparticlesmentioning
confidence: 99%
“…8c). 214 These complexes were condensed with an alkoxysilane in the presence of silicatein protein to produce metalsilica composites which demonstrated applications in sensors and catalysis. Pt-silica prepared using this method were used for SO 2 sensing while Pd-silica hybrids were successfully tested for Heck reactions for carbon-carbon coupling.…”
Section: Supporting Metals and Functional Metallic Nanoparticlesmentioning
confidence: 99%